2011
DOI: 10.9734/ajea/2011/500
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Verticillium Wilt of Olive by Pseudomonas fluorescens

Abstract: Protection of pathogen-free olive planting material from infection by Verticillium dahliae during plant propagation and/or at planting would help in the management of Verticillium wilt of olive. Despite the importance for rhizosphere functioning, rhizobacterial Pseudomonas spp. have been mainly studied in a cultivation-based manner. In this study, 8 isolates of Pseudomonas fluorescens obtained from roots of olive plants were tested for suppression of Verticillium wilt in nursery-produced olive planting stocks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 26 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…Many strains of Bacillus and Pseudomonas have been used in agriculture as biocontrol agents against several diseases caused either by fungi or bacteria [ 54 ]. Sanei [ 55 ] reported that eight isolates of Pseudomonas fluorescens inhibited Verticillium ’s microsclerotia germination. The long-term endurance of microsclerotia and the fact that they cause the initial infections, make them direct targets of biocontrol of Verticillium dahliae [ 15 , 55 ].…”
Section: Beneficial Microorganisms Against Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…Many strains of Bacillus and Pseudomonas have been used in agriculture as biocontrol agents against several diseases caused either by fungi or bacteria [ 54 ]. Sanei [ 55 ] reported that eight isolates of Pseudomonas fluorescens inhibited Verticillium ’s microsclerotia germination. The long-term endurance of microsclerotia and the fact that they cause the initial infections, make them direct targets of biocontrol of Verticillium dahliae [ 15 , 55 ].…”
Section: Beneficial Microorganisms Against Pathogensmentioning
confidence: 99%
“…Sanei [ 55 ] reported that eight isolates of Pseudomonas fluorescens inhibited Verticillium ’s microsclerotia germination. The long-term endurance of microsclerotia and the fact that they cause the initial infections, make them direct targets of biocontrol of Verticillium dahliae [ 15 , 55 ]. Furthermore, Markakis et al [ 56 ] showed that the application of Paenibacillus alvei K165 was also associated with the reduction of microsclerotia germination.…”
Section: Beneficial Microorganisms Against Pathogensmentioning
confidence: 99%
“…Strains of Pseudomonas spp. have been isolated from the olive rhizosphere (and elsewhere), and proved to suppress VWO in young, nursery-produced plants (Mercado-Blanco et al, 2004 ; Sanei and Razavi, 2011 ; Triki et al, 2012 ; Gómez-Lama Cabanás et al, 2018 ). One of the best known BCA against VWO is P. fluorescens PICF7 (Prieto et al, 2009 ; Martínez-García et al, 2015 ).…”
Section: Harnessing Beneficial Components Of Belowground Microbiota Tmentioning
confidence: 99%
“…For instance, application of microbial antagonists in pathogen‐free certified olive plants during the propagation process at nurseries has been proposed (Tjamos, ). There are only few reports on the identification and characterization of potential BCAs against VWO, although mostly preliminary or showing limited success (Müller et al ., ; Aranda et al ., ; Sanei and Razavi, ; Mercado‐Blanco and López‐Escudero, ). Moreover, very little is known about the mechanisms involved in biocontrol activity exerted by these microbes.…”
Section: Introductionmentioning
confidence: 99%